Seasonal Changes in Thyrotropin and Thyroid Hormones in Women of Reproductive Age - Sevgül Fakı; Abbas Ali Tam; Pervin Demir; Didem Özdemir; Fatma Neslihan Çuhacı Seyrek; Ekin Yiğit Köroğlu; Oya Topaloğlu; Reyhan Ersoy; Bekir Çakır (Life)
Background: Thyroid hormones are essential for the proper functioning of the female reproductive system. Seasonal changes in thyroid hormones in women of reproductive age are not fully understood. we aimed to investigate seasonal changes in thyrotrophin and thyroid hormones in women of reproductive age. Methods: Approximately 75,000 TSH and thyroid hormone levels measured in 32,935 women between 2019 and 2023 were evaluated on a monthly and seasonal basis. The analysis of means (ANOM) method was utilized to compare the mean transformed rank of each group or the overall mean transformed rank for TSH, FT3, and FT4 values across months and seasons. Results: The differences from the maximum to minimum median values were 13.3% for TSH, 5.2% for free T3, and 5.9% for free T4. TSH levels were significantly lower in summer and autumn and higher in winter and spring than the overall transformed mean. The rate of individuals with TSH levels below 2.5 mIU/L was higher in summer and autumn than in spring and winter. Conclusions: TSH varies seasonally in women of reproductive age. It is appropriate to consider the season as well as other parameters that affect thyroid functions while evaluating thyroid hormones.